Nixon and Health Care Reform - Madden, Joshua (Kansas State University. Dept. of History, 2011)
While his legacy was undoubtedly tarnished by the scandal that cost him the Presidency – Watergate – Richard Nixon‘s efforts to reform health care, dating back to his first campaign for the Presidency against John F. Kennedy, had profound effects on almost every subsequent proposal to reform American health care policy. Those who were in positions to enact national policy changes, from members of Congress to Presidents, often used many of the same ideas in each of their proposals, some of them having tenures in the Senate lasting through several decades. When one looks at the roots of these ideas, they can almost always be traced by to Nixonian policy. In this paper, I analyze these links in an attempt to prove that health care reform should be seen as essential part of President Nixon‘s legacy, arguably as much as his actions in Vietnam or other foreign policy. Because a large part of the historical works on Nixon focus primarily on his foreign policy, health care reform is largely associated only with Democratic politicians who came onto the national stage at the same time or even after President Nixon, despite the fact that he was a central figure in shaping American health care policy. The paper I have written focuses primarily around Nixon‘s health care proposals during the 1960s and the early 1970s in their relation to the actual policy enacted later, much of it having been finally put into law just recently with the passage of the Patient Protection and Affordable Health Care Act and the Health Care and Education Reconciliation Act of 2010. I analyze why it took so long for these initiatives to be enacted into law while also exploring what gave Nixon‘s ideas the resiliency that was needed to last long enough to finally be passed through Congress. I also explore why the ideas of a Republican President shaped the liberal agenda in this country for the past forty years.
Keywords: Nixon; Health care; Kennedy; Carter; Insurance; Popular culture